Review of Sexual Maturity in the Minipig. (June 2016) - Howroyd, Paul C.; Peter, Birgit; de Rijk, Eveline
It is important to know whether the animals used in toxicology studies are sexually mature. As minipigs are being used increasingly in toxicity studies, we reviewed published data on the age of sexual maturity in the minipig. Maturity in females was assessed on the basis either of normal cycles of progesterone secretion or of the histological presence of corpora lutea and, in males, was assessed on the histological appearance of the seminiferous tubules and epididymides. In female Göttingen minipigs, the first progesterone peak was at 3.7 to 4.2 or 6.1 to 6.5 months of age. These animals were in the presence of a boar. In female Göttingen minipigs in toxicology studies, which were not in the presence of a boar, at least 1 corpus luteum in the ovaries was present in only 50% of the females by 6.5 months of age, while all were mature by 7.7 months of age. Histological maturity in the male Yucatan minipig is reported to be attained at about 4.4 months old, but in male Göttingen minipigs at about 2 months old, although the definition of maturity may have been different in the 2 studies.